Heterogeneity in union status and employee well-being - Getinet Astatike Haile; Alex Bryson; Michael J. White (Institute for the Study of Labor (IZA), 2012)
This paper examines if workplace and co-worker union status affect employee wellbeing. In contrast to the literature focusing on links between one's own membership status and wellbeing, we focus principally on non-union employees. We find that being in a union workplace and having union co-workers affect the job satisfaction of non-union employees negatively. No such a link is found with respect to job-related anxiety.
Keywords: J5; J51; J28; J82; 330; trade union; job-related anxiety; job satisfaction; linked employer-employee data; Arbeitszufriedenheit; Gewerkschaftsmitgliedschaft; Schätzung; Großbritannien